Thymus - Rezaei, Nima (IntechOpen, 2020)
The thymus gland is highly valuable, due to its functions as a part of the neuroendocrine system as well as its actions to provide a primary lymphoid microenvironment that efficiently carries T-cell differentiation and selection. This book begins with an introduction and explanation of the development of the thymus. Subsequent chapters examine a range of conditions - including environmental pollution, congenital anomalies, autoimmune diseases, and malignancies - that threaten the function and development of the thymus. The information presented herein is useful for a wide range of readers across a variety of specialties.